A novel double chamber rotary sleeve air compressor -part II: friction losses model - Alduqri, Y. A. (2020)
This paper presents the friction loss model of a novel double chamber rotary sleeve air compressor (DCRSC) concept. The compressor mechanism is similar to that of rotary compressor whereby the novelty transpires in the instalment of two rotating sleeves and a secured vane that has one end fixed to an outer sleeve and the other end to a rotor, respectively. This Part II of the paper series presents the friction losses analysis of the compressor. Thermodynamic and leakage losses models were respectively presented in Part I and Part III of this paper series. The primary aim of this paper is to formulate and analyse the friction loss model at the radial and axial contact regions of DCRSC at different rotational speed. The variations of the mechanical power and efficiency were evaluated based on the adiabatic, polytropic and isothermal thermodynamic principles as illustrated in Part I of this paper series. Considering the design simplicity of cylindrical shaped components, at maximum rotational speed of 1500 rpm, the DCRSC mechanical efficiencies are 72.43%, 66.2% and 59% when air undergoes adiabatic, polytropic and isothermal compression process, respectively. it is believed that the DCRSC is well suited for compressed air systems and air-conditioning applications.